Печенежские имена и названия - Мудрак, О.А. (Хазарский альманах, 2020)
This article offers an etymological and structural analysis of Pecheneg proper names and place names cited in “De Administrando Imperio” (written by Constantine Porphyrogenitus). The Turkic etymologies of these words are quite irregular and have a big problem with semantics. But exceeding part of Pecheneg names can be interpreted rather easily as having Ossetic language origin and can be translated from this language. Some exceptions are the words fi xed in West-Caucasian languages. The result of this investigation shows a new view of ethnic circumstances along the Khazar boarders which excludes a domination of Turkic elements.